Towards a zero carbon Alexandria - Mona Salem; Mary Zekry (Renewable Energy and Sustainable Development)
Today, the world faces an unprecedented environmental crisis. Since the Industrial Revolution, the accelerated climate change is believed to be a result of human activities; that increase the concentration of greenhouse gases (GHG) in the atmosphere – to which carbon dioxide is the largest contributor. It made a must beginning to reverse the damage inflicted on the planet. Egypt is exerting great efforts to reduce the emissions of Green House Gases and mitigate the negative impacts of climate change and deal with the main challenges that affect sustainable development. Based on an empirical analytical study, the paper examines all of the environmental factors and its effect on carbon dioxide concentration taking into consideration the characteristic of the urban fabric and conditions of Alexandria one of the biggest cities in Egypt as an applied case study of a big willing costal city. The paper simultaneously aims the management of the carbon dioxide emissions through several recommendations based on the stated study, while creating a vibrant urban environment.